Current palliative chemotherapy trials in the elderly neglect patient-centred outcome measures. Issue 1 (January 2015) - van Bekkum, Marlies L.; van Munster, Barbara C.; Thunnissen, Peter L.M.; Smorenburg, Carolien H.; Hamaker, Marije E.
Abstract Background The elderly comprise the majority of patients newly diagnosed with cancer. Despite this, little evidence-based data are available on the care of the growing number of older patients with cancer. The objective of the current study was to evaluate the characteristics and outcome measures of current clinical trials on palliative chemotherapy in elderly patients. Methods Fourteen international clinical trials registries were searched using the terms "cancer" and "elderly" to identify clinical palliative chemotherapy trials designed specifically for patients aged 70 + years. From the trial protocol, data were extracted on trial characteristics and outcome measures. Results Of 127 trials, 81% formulated one or more stringent criteria with respect to organ function; 32% excluded patients with WHO performance status (PS) 2 and 83% with PS3. Functional outcomes, health care utilisation, cognitive function after treatment, and quality of life were reported in 6%, 3%, 6%, and 31% of trials, respectively. In only 16% of trials on palliative cancer treatment, a geriatric assessment was performed at baseline. Conclusion Although recent years have seen a growing evidence base regarding fit older patients, our study suggests a lack of representative cohorts of older patients and patient-centred outcome measures in current palliative treatment trials for the elderly. Research addressing alternative outcome measures, including quality of life and impact of therapy on general functioning, cognition, and preservation of independence, and incorporation of a geriatric assessment are needed to provide elderly patients with cancer and their treating physicians with realistic information about palliative chemotherapy.